2023
DOI: 10.1186/s12870-023-04487-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tetraploids in Paper Mulberry (Broussonetia papyrifera (L.) L’Hér. ex Vent.) by colchicine

Jiana Lin,
Bingnan Zhang,
Jintuo Zou
et al.

Abstract: Background Broussonetia papyrifera (L.) L’Hér. ex Vent. has the characteristics of strong stress resistance, high crude protein content, and pruning tolerance. It is an ecological, economic, and medicinal plant. Polyploid plants usually perform better than their corresponding diploid plants in terms of nutrients, active substances, and stress resistance. Results In this study, the leaves, calli, and seeds of diploid B. papyrifera were used for tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
0
0
Order By: Relevance
“…Polyploid refers to a creature that owns three or more sets of complete chromosomes [ 6 ], which is considered the dominant feature of plant diversity [ 7 ]. Polyploidization universally occurs in nature, and numerous studies have identified that polyploid plants have a more abundant variation, whether in morphology, physiology, or biochemistry, than normal diploids [ 8 , 9 , 10 ]. For example, the triploid Eucommia has a more abundant variation amplitude and shows advantages in phenotype, photosynthesis, and secondary metabolites than diploid [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyploid refers to a creature that owns three or more sets of complete chromosomes [ 6 ], which is considered the dominant feature of plant diversity [ 7 ]. Polyploidization universally occurs in nature, and numerous studies have identified that polyploid plants have a more abundant variation, whether in morphology, physiology, or biochemistry, than normal diploids [ 8 , 9 , 10 ]. For example, the triploid Eucommia has a more abundant variation amplitude and shows advantages in phenotype, photosynthesis, and secondary metabolites than diploid [ 11 ].…”
Section: Introductionmentioning
confidence: 99%